Maternal cholecalciferol supplementation during gestation improves antioxidant capacities in gilts and piglets. Issue 1 (1st January 2021) - Zhao, Lianpeng; Mao, Zhengyu; Mou, Daolin; Huang, Long; Yang, Min; Ding, Dajing; Yan, Hui; Fang, Zhengfeng; Che, Lianqiang; Zhuo, Yong; Jiang, Xuemei; Xu, Shengyu; et al.
Abstract: Various studies have evaluated the relationship between cholecalciferol (vitamin D3 ) and reproductive performance. This study aimed at investigating the effects of maternal D3 supplementation during gestation on reproductive performance and antioxidant capacities of gilts and their offsprings. Twenty-three Landrace × Yorkshire gilts were randomly allocated into two groups and fed on one of the following two diets during gestation: control diet or D3 supplemented diet. It was found that D3 supplementation had a tendency to increase the number of total born and born alive piglets. Moreover, it elevated serum 25-hydroxycholecalciferol concentrations in gilts and newborn piglets. Besides, D3 supplementation improved the activities of antioxidant enzymes (GSH-Px, T-AOC and T-SOD) in the blood of gilts, umbilical cord and newborn piglets and piglets' liver, while serum malondialdehyde concentrations of gilts and umbilical cord were reduced in the D3 group. In addition, D3 supplementation upregulated the expression of antioxidant related genes in the placenta and piglets' liver. In conclusion, D3 supplementation during gestation might improve antioxidant capacities in gilts, placenta and in newborn piglets. Therefore, D3 supplementation has the potential to enhance the reproductive performance of gilts. HIGHLIGHTS: D3 supplementation has a significant role in the nutrition of gilts. Maternal D3 supplementation during gestation increased the number of born and born alive piglets. Maternal D3 supplementation during gestation improved the antioxidant capacities of gilts, placenta and newborn piglets.